Effect of graphite fibers on the performance of sediment microbial fuel cell. Issue 3 (10th October 2015) - Cai, Yan; Yang, Na; Ren, Yueping; Li, Xiufen; Shi, Yugang; Zhu, Rong; Wang, Xinhua
Abstract : Sediment microbial fuel cell (SMFC) is a novel technology that oxidizes organics in sludge or river/lake sediment to generate electricity using microorganisms as the biocatalyst. The electricity production performance of the SMFC was obviously enhanced by mixing conductive graphite fibers into the anodic sludge. The output voltages and the maximum power densities ( P max ) of the SMFCs increased with the increase in the added graphite fibers from 0.5 to 5 g L −1 . Ultimately, the SMFC with 5 g L −1 graphite fibers (SMFC‐5) exhibited the uppermost output voltage (154 mV) and P max (12.48 mW m −2 ), whereas that of the blank SMFC were 65 mV and 4.68 mW m −2, respectively. Moreover, the phospholipid concentrations on the anode surfaces of the SMFCs augmented with the increase of graphite fibers and the charge‐transfer resistance ( R ct ) of the corresponding anodes evidently decreased when the amount of graphite fibers was increased. Furthermore, with the increase of graphite fibers, chemical oxygen demand removal efficiencies increased from 12.72% of the blank SMFC to 44.64% of the SMFC‐5. However, the SMFC with 0.5 g L −1 graphite fibers (SMFC‐0.5) provided the highest coulombic efficiency (CE%), 2.46%. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 876–881, 2016